Convective–reactive nucleosynthesis of K, Sc, Cl and p-process isotopes in O–C shell mergers. (3rd August 2017) - Ritter, C; Andrassy, R; Côté, B; Herwig, F; Woodward, P R; Pignatari, M; Jones, S
Abstract: We address the deficiency of odd-Z elements P, Cl, K and Sc in Galactic chemical evolution models through an investigation of the nucleosynthesis of interacting convective O and C shells in massive stars. 3D hydrodynamic simulations of O-shell convection with moderate C-ingestion rates show no dramatic deviation from spherical symmetry. We derive a spherically averaged diffusion coefficient for 1D nucleosynthesis simulations, which show that such convective–reactive ingestion events can be a production site for P, Cl, K and Sc. An entrainment rate of 10 −3 M⊙ s −1 features overproduction factors OPs ≈ 7. Full O–C shell mergers in our 1D stellar evolution massive star models have overproduction factors OPm > 1 dex but for such cases 3D hydrodynamic simulations suggest deviations from spherical symmetry. γ-process species can be produced with overproduction factors of OPm > 1 dex, for example, for 130, 132 Ba. Using the uncertain prediction of the 15 M⊙, Z = 0.02 massive star model (OPm ≈ 15) as representative for merger or entrainment convective–reactive events involving O- and C-burning shells, and assume that such events occur in more than 50 per cent of all stars, our chemical evolution models reproduce the observed Galactic trends of the odd-Z elements.